2011
DOI: 10.1149/1.3625282
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependent Emission of Strontium-Barium Orthosilicate (Sr2−xBax)SiO4:Eu2+ Phosphors for High-Power White Light-Emitting Diodes

Abstract: Samples of (Sr 1.9Àx Ba x)SiO 4 :Eu 0.1 were synthesized by a solid-state reaction. The maximum emission intensity under 460 nm excitation was obtained at a Ba content, x, of 1.6. All Sr 1.9Àx Ba x SiO 4 :Eu 0.1 samples except for Ba 1.9 SiO 4 :Eu 0.1 exhibited a temperature-driven blue-shift of the emission band. The thermostability of emission in (Sr 1.9Àx Ba x)SiO 4 :Eu 0.1 depended strongly on the Ba/Sr ratio. The thermal quenching temperature reached its maximum at a Ba concentration x of 1.2-1.6 and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…However, there is a blue-shift of the emission spectra from 485 to 467 nm with temperature increasing from 300 to 550 K. Similar results have been observed in NaCaPO 4 :Eu 2+ [31], Ca 3 Mg 3 (PO 4 ) 4 :Eu 2+ [32] and Ca 2 BO 3 Cl:Eu 2+ [33]. It is attributed to the thermally active phonon-assisted tunneling from the excited states of low energy emission band to excited states of high energy emission band in the configuration coordinated diagram [34,35], because there are two inequivalent sites for Eu 2+ to occupy in CaZr 4 (PO 4 ) 6 . Moreover, the electrons population in the upper vibration level of the Eu 2+ excited state becomes dominant under phonon assistance at high temperature.…”
Section: Uv Emission and Excitation Spectra Of Casupporting
confidence: 80%
“…However, there is a blue-shift of the emission spectra from 485 to 467 nm with temperature increasing from 300 to 550 K. Similar results have been observed in NaCaPO 4 :Eu 2+ [31], Ca 3 Mg 3 (PO 4 ) 4 :Eu 2+ [32] and Ca 2 BO 3 Cl:Eu 2+ [33]. It is attributed to the thermally active phonon-assisted tunneling from the excited states of low energy emission band to excited states of high energy emission band in the configuration coordinated diagram [34,35], because there are two inequivalent sites for Eu 2+ to occupy in CaZr 4 (PO 4 ) 6 . Moreover, the electrons population in the upper vibration level of the Eu 2+ excited state becomes dominant under phonon assistance at high temperature.…”
Section: Uv Emission and Excitation Spectra Of Casupporting
confidence: 80%
“…It is well known that phosphors must have the ability to resist to the temperatures generated during working of LEDs (typically between 90 and 100 1C; for higher-power LEDs, the temperature can be up to 150 1C). 87 So the as-synthesized ZnGeN 2 :Mn 2+ phosphor possesses a potential appliance value in the white LED field. Moreover, we also observed that the FWHM of the emission band increases from 54 nm to 75 nm as the temperature increased.…”
Section: Temperature-dependent Photoluminescence Behaviormentioning
confidence: 99%
“…32 The main disadvantages of the thiogallates are their chemical and thermal instability. 63 Under blue excitation, these phosphors have the highest PL intensity when x = 1.6, giving broad green emission due to the Eu 2+ ions that occupy 10-coordinated sites in the lattice. Some thiogallate phosphors are also susceptible to emission spectral shifts and spectral broadening at elevated temperatures.…”
Section: (4) Phosphors For Blue Led Approachmentioning
confidence: 99%
“…For example, measurements on BaGa 2 S 4 :Eu 2+ show an emission peak shift from 503 nm (FWHM = 42 nm) to 488 nm (FWHM = 70 nm) 61 when the temperature is increased from 77 to 450 K. (b) Orthosilicates: The family of silicates that crystallize in the orthorhombic structure, (M 2+ ) 2 SiO 4 where M = Ba,Sr have received interest for potential use in SSL due to the ability to tune their emission colors by controlling the Ba/Sr ratio. 63 The thermal quenching of (Ba/ Sr) 2 SiO 4 is reported to be 30% at 150°C. 63 Under blue excitation, these phosphors have the highest PL intensity when x = 1.6, giving broad green emission due to the Eu 2+ ions that occupy 10-coordinated sites in the lattice.…”
Section: (4) Phosphors For Blue Led Approachmentioning
confidence: 99%